Beyond, Beside, and Between the Acts: Woolf, Derrida, and the Politics of a Middle Voice - Carlson, Christy (My University, 1991)
In this thesis, I examine the discourses of Virginia Woolf and Jacques Derrida each from the perspective of the other in an attempt to discuss the insights and limitations of each theory. I begin by considering each writer's version of what I will call the middle voice, a notion that serves as the point of departure for my examination of the linguistic processes of graft and disengagement in both Woolf and Derrida. Turning to the philosophical and political problems that arise when these writers put their versions of the middle voice into practice, I discuss their mutual desire (and inevitable failure) to oppose and displace totalization. Despite the similarity of these projects, however, I argue that they arise from distinct relations to subjectivity and, as a result, different imperatives. Next, I consider the (non)principle that permits and enables these notions (that is, the ungraspable because always already divided origin and the decentralizing or (self)effacing self): the logic of supplementarity. This logic allows me to interrogate further the faulty unity that masks a duplicity by showing how Between the Acts disrupts and deconstructs limits of representation. Finally, I reconsider the middle voice, this time from Emile Benveniste's position, thus re-turning, once again, to the problem of totalization; I "end" by proposing a pragmatic (but necessarily problematic) praxis, which combines both a Derridean and a Woolfian approach, and that yields a discourse which promises both a critique of totalization and a political vision.
Keywords: English Language and Literature; English Language and Literature